2020
DOI: 10.5267/j.msl.2019.8.015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of website brand equity, e-brand experience on e-loyalty: The mediating role of e-satisfaction

Abstract: This paper analyses the role of online satisfaction (e-satisfaction) as a mediator in the relationship between website brand equity, online brand experience (e-brand experience) and online loyalty (eloyalty) in the context of shopping online in Vietnam. The data for this study were gathered through mail questionnaires which were distributed to target participants who reported their consumption experience with shopping online through website. The survey was conducted at three big cities of Vietnam with the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 63 publications
2
14
0
3
Order By: Relevance
“…In our study, brand association refers to everything related to the brand in consumers' minds. Brand association can help consumers determine the relevance of both the parent brand and extended brands [103]. We believe that brand association will affect brand loyalty in the context of cultural and artistic visitor attractions and mixed reality souvenir shops.…”
Section: Brand Association and Brand Loyaltymentioning
confidence: 95%
“…In our study, brand association refers to everything related to the brand in consumers' minds. Brand association can help consumers determine the relevance of both the parent brand and extended brands [103]. We believe that brand association will affect brand loyalty in the context of cultural and artistic visitor attractions and mixed reality souvenir shops.…”
Section: Brand Association and Brand Loyaltymentioning
confidence: 95%
“…Therefore, the population of the present study involves consumers of E‐brands in China who use social media to interact with brands. E‐brand refers to the online brand, which uses internet and social media channels as the medium to position and endorse the brand among consumers in the marketplace (Quan et al, 2020). The E‐brand consumers of China having exposure to SMMAs are targeted population of the current study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, researchers found that website brand equity had an influence on consumers' online experience and online loyalty. 53 Interactive music in the design of an e-commerce website could create a more engaging consumer experience and influence consumer's behavioral intention. 54 These factors need to be further researched in the future studies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%